Ischemic preconditioning protects against cardiac ischemia reperfusion injury without affecting succinate accumulation or oxidation. (October 2018) - Pell, Victoria R.; Spiroski, Ana-Mishel; Mulvey, John; Burger, Nils; Costa, Ana S.H.; Logan, Angela; Gruszczyk, Anja V.; Rosa, Tiziana; James, Andrew M.; Frezza, Christian; Murphy, Michael P.; Krieg, Thomas
Abstract: Ischemia-reperfusion (IR) injury occurs when blood supply to an organ is disrupted and then restored, and underlies many disorders, notably myocardial infarction and stroke. While reperfusion of ischemic tissue is essential for survival, it also initiates cell death through generation of mitochondrial reactive oxygen species (ROS). Recent work has revealed a novel pathway underlying ROS production at reperfusion in vivo in which the accumulation of succinate during ischemia and its subsequent rapid oxidation at reperfusion drives ROS production at complex I by reverse electron transport (RET). Pharmacologically inhibiting ischemic succinate accumulation, or slowing succinate metabolism at reperfusion, have been shown to be cardioprotective against IR injury. Here, we determined whether ischemic preconditioning (IPC) contributes to cardioprotection by altering kinetics of succinate accumulation and oxidation during IR. Mice were subjected to a 30-minute occlusion of the left anterior descending coronary artery followed by reperfusion, with or without a protective IPC protocol prior to sustained ischemia. We found that IPC had no effect on ischemic succinate accumulation with both control and IPC mice having profound increases in succinate compared to normoxia. Furthermore, after only 1-minute reperfusion succinate was rapidly metabolised returning to near pre-ischemic levels in both groups. We conclude that IPC does not affect ischemic succinate accumulation, or its oxidation at reperfusion. Highlights: Succinate accumulates during cardiac ischemia and its oxidation drives ROS production upon reperfusion. IPC does not affect succinate accumulation or oxidation during cardiac IR injury. Changes in succinate metabolism do not contribute to IPC.